2001
DOI: 10.1002/ajhb.10002
|View full text |Cite
|
Sign up to set email alerts
|

Fat distribution in venezuelan children and adolescents estimated by the conicity index and waist/hip ratio

Abstract: This study compares the conicity index (C) with the waist/hip ratio (WHR) in a cross-sectional sample of Venezuelan children (n = 784 boys and n = 735 girls), 3 to 16 years of age. Distributions of C and WHR were compared in Box-plot diagrams. Regression analysis was used to examine the relationship between indices by age and sex. Conicity captured more outliers in the distribution than WHR and explained 33% to 62% of the variability in WHR in three age groups. The influence was stronger in females during adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…Our results showed that CI is a poor predictor of trunk fat in children aged 3–5 years, confirming results from predominantly older children 12. Previous workers have only compared the distribution of CI with WHtR 23 or studied CI as an index of regional fat distribution in hepatic steatosis 24.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results showed that CI is a poor predictor of trunk fat in children aged 3–5 years, confirming results from predominantly older children 12. Previous workers have only compared the distribution of CI with WHtR 23 or studied CI as an index of regional fat distribution in hepatic steatosis 24.…”
Section: Discussionsupporting
confidence: 86%
“…Other anthropometric indices used to indicate a more central fat pattern include the conicity index (CI) and the waist-to-height ratio (WHtR). CI evaluates waist circumference in relation to height and weight (22), but has been used infrequently in children (12,23,24). In contrast, support for WHtR is increasing (25) and initial studies suggest that it is strongly related to cardiovascular risk in growing children (13,15,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…C-index has been identified as an important parameter in the evaluation of body fat distribution in the paediatric population ( 45 ) . Although it has performed satisfactorily in the identification of android fat in children, its routine use may be hampered by the lack of specific cut-off points.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al (38) (38) . Alternatively, the conicity index is a simple and, in the absence of sophisticated equipment, can be used as a measure of body fat distribution in children (39) . The BMI is widely reported as a diagnostic tool for obesity.…”
Section: Discussionmentioning
confidence: 99%